Mediation, an Annotated Bibliography, by E. Levin and D.V. De Santis. - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Mediation, an Annotated Bibliography," by E. Levin & D.V. De Santis.